The fate of nitrate in intertidal permeable sediments. - Hannah K Marchant; Gaute Lavik; Moritz Holtappels; Marcel M M Kuypers (PLoS ONE, 2014)
Coastal zones act as a sink for riverine and atmospheric nitrogen inputs and thereby buffer the open ocean from the effects of anthropogenic activity. Recently, microbial activity in sandy permeable sediments has been identified as a dominant source of N-loss in coastal zones, namely through denitrification. Some of the highest coastal denitrification rates measured so far occur within the intertidal permeable sediments of the eutrophied Wadden Sea. Still, denitrification alone can often account for only half of the substantial nitrate (NO3-) consumption. Therefore, to investigate alternative NO3- sinks such as dissimilatory nitrate reduction to ammonium (DNRA), intracellular nitrate storage by eukaryotes and isotope equilibration effects we carried out 15NO3- amendment experiments. By considering all of these sinks in combination, we could quantify the fate of the 15NO3- added to the sediment. Denitrification was the dominant nitrate sink (50-75%), while DNRA, which recycles N to the environment accounted for 10-20% of NO3- consumption. Intriguingly, we also observed that between 20 and 40% of 15NO3- added to the incubations entered an intracellular pool of NO3- and was subsequently respired when nitrate became limiting. Eukaryotes were responsible for a large proportion of intracellular nitrate storage, and it could be shown through inhibition experiments that at least a third of the stored nitrate was subsequently also respired by eukaryotes. The environmental significance of the intracellular nitrate pool was confirmed by in situ measurements which revealed that intracellular storage can accumulate nitrate at concentrations six fold higher than the surrounding porewater. This intracellular pool is so far not considered when modeling N-loss from intertidal permeable sediments; however it can act as a reservoir for nitrate during low tide. Consequently, nitrate respiration supported by intracellular nitrate storage can add an additional 20% to previous nitrate reduction estimates in intertidal sediments, further increasing their contribution to N-loss.